Solution of the Burgerâs Equation for Longitudinal Dispersion Phenomena Occurring in Miscible Phase Flow through Porous Media - Mitesh S. Joshi; Narendrasinh B. Desai; Monika N. Mehta (Journal of Engineering and Technological Sciences, 2012)
An approximate solution of longitudinal dispersion phenomena occurring in two phase miscible fluid flow through porous media has been obtained by using the group theoretic approach. The longitudinal dispersion coefficient is assumed to be directly proportional to the concentration of the fluid for a distance x and at any time t > 0. The graphical representation for the concentration of the fluid for a distance x and at time t > 0 has been obtained using Mat lab coding.